Section 59 Industrial Relations Act 1967: The Forgotten Remedy - Syed Ahmad, Sharifah Suhana (Journal of Malaysian and Comparative Law, 2019)
Section 8(b) of the Employment Act 1955 provides that nothing in any contract of service shall in any manner restrict the right of any employee who is a party to such contract to participate in the activities of a registered trade union, whether as an officer of such union or otherwise. This is further reinforced by section 7, which provides that any term or condition in a contract of service which is less favourable to an employee governed by the Employment Act than a term or condition prescrribed by the Act itself shall be void and of no effect to that extent, and the more favourable provision of the Act is to be substituted therefor.